Buletin Peternakan : KUALITAS SOSIS DAGING SAPI YANG DIFORTIFIKASI DENGAN MINYAK IKAN KOD DAN MINYAK JAGUNG DAN DIPROSES MENGGUNAKAN METODE PEMASAKAN YANG BERBEDA - Rio Olympias Sujarwanta (Peternakan UGM, 2016)
This study was conducted to find out quality of beef sausages fortified with cod and corn oil and processed with different cooking methods. The sausages were made of beef, cod oil, corn oil, tapioca flour, skimmed milk, salt, pepper, garlic, angkak, and ice, with the ratio of cod oil and corn oil of 2.9 : 7.1; 2.4 : 7.6; and 1.9 : 8.1. All sausages ingredients were mixed and then filled in the casing. The raw sausages were cooked using steaming and vacuum steaming for 30 minutes. The sausages were then analyzed for chemical composition (moisture, protein, and fat contents), physical quality (pH, water holding capacity, and tenderness), and fatty acids profile (omega 3 and omega 6 ratio). The data of chemical composition and physical quality were analyzed statistically using analysis of variance (factorial pattern = 3 factors of oil ratio x 2 factors of cooking method) and the differences between means were tested by Duncan’s new Multiple Ranges Test. The data of fatty acids profile were analyzed descriptively.